2021
DOI: 10.1007/s00203-021-02193-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the oscillating magnetic field on airborne fungal

Abstract: This study shows that some species of fungi are affected by the magnetic field, which should be taken into account in studies of airborne fungal and air quality. The aim of this paper was to evaluate the effect of the oscillating magnetic field (OMF) on the behavior of colonies of three fungi genus growth in different culture mediums. The stains were: Aspergillus niger, Cladosporium cladosporioides and Penicillium citrinum and were inoculated in 90 mm Petri dishes with: Malt Extract Agar (MEA), Sabouraud Dextr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Numerous studies have shown that non-uniform magnetic fields can introduce variations in the response of biological systems, affecting the results of controlled biotechnological experiments [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. By addressing non-uniformity through polygonal coil designs and dimension adjustments, the understanding and applicability of electromagnetic technologies in various biotechnology studies can be advanced [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that non-uniform magnetic fields can introduce variations in the response of biological systems, affecting the results of controlled biotechnological experiments [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. By addressing non-uniformity through polygonal coil designs and dimension adjustments, the understanding and applicability of electromagnetic technologies in various biotechnology studies can be advanced [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent research indicates that electromagnetic fields can stimulate or inhibit different biological systems [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], such as the growth of plants [ 13 ], fruits [ 14 ], and microorganisms [ 15 ]. Similarly, they affect cells in the human [ 16 ] and animal [ 17 ] body by stimulating or inhibiting different cellular processes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation